Problem-Based Learning Model for Teaching Writing: A Literature Review - Nurul Aryanti; Welly Ardiansyah; Murwani Ujihanti (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
Many researchers have claimed the success of the application of problem-based learning in many fields of study. This learning model is in line with the constructivist principles, in which students are in the centre of the learning process. Moreover, problem-based learning model provides the opportunity for students not only to develop their hard skills, but also soft skills. In addition, it also strives to help students become independent and self-regulated learners. This is one of the main advantages of applying the learning model. This article attempts to provide a short review of problem-based learning model in teaching writing. Furthermore, the discussion will also focus on the issue by looking at some explanation found in accounting for the needs of the learning model in the 21st century-language learning